Heracles' itch: An analysis of the first case of male uterine displacement in Greek literature - Blanco, C (Cambridge University Press, 2020)
Scholars have long grappled with the nature of Heracles’ νόσος and his consequent feminization in Sophocles’ Women of Trachis (= Trachiniae). Despite being triggered by a poisonous garment, which acts by means of magic incantation, the evolution of Heracles’ symptoms is described as a clinical case. Yet, making sense of his feminization from a scientific perspective has proven hard. In this paper, I investigate the symptoms experienced by Heracles, which Sophocles generically refers to as νόσος. The first part focusses on Sophocles’ description of erôs as a disease in Trachiniae. I then move on to dividing Heracles’ symptoms into two categories, which I will call νόσος1 and νόσος2. The erotic passion for Iole which Heracles naturally experiences in the first part of the tragedy will be denoted by νόσος1, whereas νόσος2 will refer to the magic-induced symptoms from which he suffers in the second and final part. In the final section of the paper I will seek to provide a scientific explanation for νόσος2 and, ultimately, to describe the medical reasons behind Heracles’ feminization.